KEKUATAN DIKSI DALAM BUKU PUISI TARIAN HUJAN - I Gusti Ayu Agung Mas Triyadnyani (Sintesis, 2019)
This paper examines the poems of Jane Ardhaneshwari, a poet who published his latest poem in theprestigious Ubud Writers Readers Festival 2017. The poetry book of Dancing Rain is interesting toobserve, especially in terms of language usage. Dictation is the dominant force that appears in Jane'spoems. Therefore, the theory used to analyze is stylistic theory. The beauty of the language in theDancing Rain can be seen from the creation of original dictions.